PCR ribotypes of Clostridioides difficile across Texas from 2011 to 2018 including emergence of ribotype 255. Issue 1 (1st January 2020) - Gonzales-Luna, Anne J.; Carlson, Travis J.; Dotson, Kierra M.; Poblete, Kelley; Costa, Gabriela; Miranda, Julie; Lancaster, Chris; Walk, Seth T.; Tupy, Shawn; Begum, Khurshida; Alam, M. Jahangir; Garey, Kevin W.
ABSTRACT: Clostridioides difficile infection (CDI) is the most prevalent healthcare-associated infection in the United States and carries a significant healthcare system burden. As part of an ongoing, active surveillance system of C. difficile throughout Texas, the objective of this study was to assess changes in C. difficile ribotypes of clinical isolates obtained from hospitalized patients in Texas over the past seven years. Fifty hospitals located in Texas, USA sent C . difficile positive stool specimens to a centralized laboratory for PCR ribotyping and toxin characterization between 2011 and 2018. Data collected included specimen collection date, patient age, and sex. Strain genotypes were compiled, and changes in ribotype distribution over time were assessed. Overall, 7796 samples were ribotyped from predominately female patients (58.4%) aged 62 ± 19 years. Samples were obtained from all geographic regions of Texas including Houston/Southwest region ( n  = 5129; 85%), Dallas/North Texas ( n  = 579, 9.6%), Central Texas ( n  = 164; 2.7%), and South Texas ( n  = 162; 2.6%). The 10 most common ribotypes comprised 73% of all isolates tested during the study period. The most common ribotypes were 027 (17.5%), followed by 014–020 (16.1%), 106 (11.6%), and 002 (9.1%). The prevalence of ribotypes 027, 001, and 078–126 declined significantly over time, while ribotypes 106 and 054 increased in prevalence ( P  < 0.001). Furthermore, the emergence of a novel ribotype 255 strain was observed. Differences in ribotype distribution were also noted based on age and geographic distribution ( P  < 0.001, each). This seven-year study demonstrated changing molecular epidemiology of C. difficile in Texas, including the emergence of a novel ribotype 255.